Phylogenetics of Polygonaceae with an emphasis on the evolution of Eriogonoideae (2008)
Polygonaceae has long been recognized as a monophyletic family but the circumscription of groups within it has been in constant flux. Two groups currently recognized are the subfamilies Eriogonoideae and Polygonoideae. An analysis using three chloroplast regions (rbcL, matK, and ndhF) and increased taxon sampling of Eriogonoideae does not support this delimitation. The second intron and portions of the flanking exons of the nuclear gene LEAFY, were used to explore phylogenetic utility in Polygonaceae. The intron showed high levels of variability and was useful at low taxonomic levels, but not alignable outside of Eriogonum and allied genera. Phylogenetic analysis of data from the flanking exons of the second intron of LEAFY generally supports the major groupings found in the chloroplast analysis. A new definition of the subfamilies is proposed. Polygonoideae is restricted to what has been recognized as tribes Persicarieae, Rumiceae, and Polygoneae, with the addition of Muehlenbeckia. Eriogonoideae now includes Antigonon, Brunnichia, Coccoloba, Ruprechtia, Triplaris, and Eriogonum and allied genera. The genera Eriogonum and Chorizanthe are nonmonophyletic.